The Effect of Cancer Patients' and Their Family Caregivers' Physical and Emotional Symptoms on Caregiver Burden. Issue 2 (March 2018) - Johansen, Safora; Cvancarova, Milada; Ruland, Cornelia
Abstract : Background: Although there is significant evidence that the family caregivers (FCs) of cancer patients can experience significant caregiver burden and symptoms, less is known about the relationships between FCs and patient characteristics that influence caregiver burden. Objective: The purpose of this study was to examine the effect of cancer patients' and FCs' symptoms and demographic characteristics on caregiver burden at initiation of the patients' radiation treatment. Methods: Two hundred eighty-one dyads of FCs and cancer patients who received a diagnosis of breast, prostate, melanoma, lymphoma, and head and neck cancers were recruited at the beginning of the patients' radiation treatment. Measures of depression, sleep disturbance, fatigue, social support, and self-efficacy were obtained from both FCs and cancer patients. The family caregivers were also assessed for caregiver burden. Associations between patients' and caregivers' symptoms and demographic characteristics and caregiver burden were investigated using multivariate analyses. Results: There were significant associations between caregiver burden and the patient-related variables such as self-efficacy ( P = .02), sleep disturbance ( P = .03), and social support ( P = .04). Among FC-related variables, higher scores of depression ( P < .01), fatigue ( P < .01), and symptoms ( P < .01) were significantly associated with higher caregiver burden. Being a female, either as a patient or FC, increased the likelihood of experiencing fatigue and sleep disturbance. Conclusion: Caregiver burden in FCs is influenced by interplay of patients' and their own symptoms and problems. These interdependencies exist from the beginning of treatment. Implications for Practice: Nurses should systematically assess the problems and symptoms of the patients and FCs and support them from the time of diagnosis to help prevent symptom development and deterioration.